Goethe yearbook, Volume XXVII publications of the Goethe Society of North America - Simpson, Patricia A. 1958-; Tautz, Birgit 1967-; Franzel, Sean 1976- (Camden House, 2020)
A new Forum section focuses on the impact of Digital Humanities on Goethe scholarship and on eighteenth-century German Studies, alongside articles on a diverse range of authors and topics